Insight into the high proportion application of biomass fuel in iron ore sintering through CO-containing flue gas recirculation. (20th September 2019) - Gan, Min; Ji, Zhiyun; Fan, Xiaohui; Zhao, Yuanjie; Chen, Xuling; Fan, Yong
Abstract: Biomass energy has been widely regarded as a potential alternative to fossil fuels for abating CO2 emission and gaseous pollutants in iron ore sintering process. In this investigation, the CO-containing flue gas recirculating method was proposed, with its essence of CO reburning to improve sintering performance with high biomass replacement proportion. Results show that biomass fuels replacing more than 20% coke breeze would result in obvious drop of sinter quality due to the shortened high-temperature duration and minerals melting zone. Circulating CO-containing flue gas into sintering bed improved sinter quality significantly as the secondary combustion of CO optimized thermal state. The appropriate replacement proportion of biomass fuel was improved to 40%, and the energy utilization efficiency was increased from 87.25% to 89.62%, which was even higher than that of using coke breeze only. Compared with the case no flue gas circulated, circulating CO-containing flue gas into sintering bed improved the reduction capacity of CO x, NO, and SO2 from 18.65%, 26.76%, and 38.15%–31.78%, 45.07%, and 44.51%, respectively. Research findings facilitates the application of high-proportion biomass fuels in practical sintering plants with high energy utilization efficiency as well. Graphical abstract: Image 1016537 Highlights: High reactivity of biomass led to lower energy efficiency and replacement proportion. A novel approach for improving sintering with high proportion biomass was developed. Novel approach has great potential in clean and efficient sintering production.